Akhlaq Pendidik dan Peserta Didik dalam Perspektif Pendidikan Agama Islam - Yazidul Busthomi Khozin; M. Zainul Mukhtar (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Akhlaq is a condition or trait that has penetrated the soul and becomes a personality that causes various kinds of actions in a spontaneous way without doing any prior thought. Morals is the science that teaches humans to do good and prevent evil actions in their interactions. The morality of educators in the perspective of Islamic religious education is as follows: 1. Accepting questions raised by students and being patient with them, 2. Not rushing in all matters, 3. Sitting with dignity with calmness and bowing your head. The morals of students in the perspective of Islamic religious education are as follows: 1). Starting to greet and ask permission to enter, 2). A little talk in front of the teacher, 3). Does not speak as long as the teacher is not asked.